Sustaining Scholarly Infrastructures through Collective Action: The Lessons that Olson can Teach us. Issue 1 (27th December 2017) - Neylon, Cameron
The infrastructures that underpin scholarship and research, including repositories, curation systems, aggregators, indexes and standards, are public goods. Finding sustainability models to support them is a challenge due to free-loading, where someone who does not contribute to the support of an infrastructure nonetheless gains the benefit of it. The work of Mancur Olson (1965 ) suggests that there are only three ways to address this for large groups: compelling all potential users, often through some form of taxation, to support the infrastructure; providing non-collective (club) goods to contributors that are created as a side-effect of providing the collective good; or implementing mechanisms that lower the effective number of participants in the negotiation (oligopoly). In this paper, I use Olson's framework to analyse existing scholarly infrastructures and proposals for the sustainability of new infrastructures. This approach provides some important insights. First, it illustrates that the problems of sustainability are not merely ones of finance but of political economy, which means that focusing purely on financial sustainability in the absence of considering governance principles and community is the wrong approach. The second key insight this approach yields is that the size of the community supported by an infrastructure is a critical parameter. Sustainability models will need to change over the life cycle of an infrastructure with the growth (or decline) of the community. In both cases, identifying patterns for success and creating templates for governance and sustainability could be of significant value. Overall, this analysis demonstrates a need to consider how communities, platforms, and finances interact and suggests that a political economic analysis has real value.